Mental health in medical students: time to act. (28th June 2019) - Awad, Fady; Awad, Mina; Mattick, Karen; Dieppe, Paul
Summary: Background: Mental health problems are prevalent amongst medical students. However, many students delay seeking medical help or support from the medical school for a variety of reasons, including a fear of facing fitness to practice proceedings. Tackling this problem of awareness and delayed presentation will need a strong and dedicated focus at all stages, with prevention being of great importance. Methods: A conference dedicated to mental health and well‐being was organised for students of all years. The first part of the conference centred on well‐being dilemmas and the second part focused on discussing important issues in small group sessions. Results: Students were divided into eight groups and each group suggested improvements to the course that they felt would improve mental health and well‐being. The main suggestions raised were: reassurance that the disclosure of mental health problems would not automatically result in fitness to practice proceedings; separate academic and pastoral roles of tutors; open up the topic of mental health and well‐being more frequently during the programme; improve knowledge about the availability of support services; and have mentors who are at an earlier stage in postgraduate training (e.g. junior doctors). Discussion: It is necessary to tackle the prevalent myths about this topic. Many students are unaware of the support services available. This conference has therefore sought to increase awareness of the topic. An approach is also now needed to identify those who need extra help. The authors strongly advocate opening up this topic throughout the course in the context of a dedicated conference, for example. Many students are unaware of the support services available The authors strongly advocate opening up this topic throughout the course in the context of a dedicated conference …